PROCESS OF CIGARETTE DESIGNING INDUSTRY IN TONGA SUBSCRIPTION OF KESU 'REGENCY OF NORTH TORAJA - Reski Rante Langngan; Thamrin Mappalahere; Yabu M. Yabu M. (Universitas Negeri makassar, 2019)
The problems of this research are; 1) The process of making wall decorations in the village of Tonga Kesu District 'North Toraja District? 2) Inhibiting and supporting factors in making wall decoration in Tonga Village Kesu District '. The type of this research is survey research that aims descriptive qualitative to describe the process of making carving wall hangings and supporting factors and inhibitors experienced by crafters. In this research, there are 2 groups of artisans in Tonga Village in the North and the South. The result shows that the technique of making wall decoration is done manually from the material processing process until the final step of manufacture by using the tools that have been provided. The first stage in making these wall decorations are: Measurement and cutting of wood, second stage of surface and wooden cuttings, third stage of surface painting and periphery, stage four painting with black paint, the sixth stage of pattern making, the seventh stage of engraving and stage next coloring carving and the last is finishing. 3) Supporting factors in the process of making wall decoration of wooden decoration are easy to obtain, the availability of labor, the availability of tools and additional materials and the existence of self-taught craftsmen. Inhibiting factors are lack of capital, high cost of raw materials, equipment that tends to be a very simple, production marketing process that is only traditional.